2020
DOI: 10.5817/cp2020-3-1
|View full text |Cite
|
Sign up to set email alerts
|

To thine communication partner be true: The effect of presentation consistency on perceived authenticity and liking after making a first impression online

Abstract: This experiment examines the effects of presentation consistency on perceived authenticity and liking in computer-mediated communication, differentiating between profile views and short online text-based conversations. The experimental design is a 2 (presentation-consistent vs. -inconsistent) × 2 (profile view vs. short conversation) between-subjects experiment using university students (N = 173) in Singapore. Results show higher perceived authenticity (η2p = .29) and liking (η2p = .16) after short conversatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…To some extent, the authenticity model can help us understand the influence of self-generated inconsistency because it implicates that selfgenerated inconsistency could lead to negative interpersonal evaluations (i.e., harm the authenticity of a presenter). In line with this proposition, a recent experimental study confirmed that online presentation inconsistencies induced negative evaluations of a target person's authenticity and likeability (Tang et al, 2020). Similarly, prior research found that participants viewed a target whose online presentations deviated from his/her offline performances (i.e., observers' base-rate knowledge) as less trustworthy but more hypocritical (DeAndrea and Walther, 2011).…”
Section: Perceiving Inconsistent Information On Social Mediamentioning
confidence: 56%
See 4 more Smart Citations
“…To some extent, the authenticity model can help us understand the influence of self-generated inconsistency because it implicates that selfgenerated inconsistency could lead to negative interpersonal evaluations (i.e., harm the authenticity of a presenter). In line with this proposition, a recent experimental study confirmed that online presentation inconsistencies induced negative evaluations of a target person's authenticity and likeability (Tang et al, 2020). Similarly, prior research found that participants viewed a target whose online presentations deviated from his/her offline performances (i.e., observers' base-rate knowledge) as less trustworthy but more hypocritical (DeAndrea and Walther, 2011).…”
Section: Perceiving Inconsistent Information On Social Mediamentioning
confidence: 56%
“…This study highlights the central role of perceived authenticity in online interpersonal perception. Considering the surge of misinformation in current online contexts, increasing research attention has been given to the role of authenticity ( Marwick and Boyd, 2011 ; Wotipka and High, 2016 ; Lee, 2020 ; Tang et al, 2020 ). Recent research has proposed that the perception of authenticity is bonded with the sense of (in)consistency concerning observers’ base-rate knowledge ( Lee, 2020 ), while the present study further suggests that an interrelationship exists between (in)consistency and authenticity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations